ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT WAJIB PAJAK ORANG PRIBADI DALAM MENGGUNAKAN E-FILING - Azzahra, Fika; Setyawati, Wiwit (Jurnal Ilmiah Akuntansi dan Keuangan (JIAKu), 2023)
This research was conducted to determine the influence of perceived convenience, perceived usefulness, and security and confidentiality on individual taxpayers' interest in using E-Filing. The research method used is a quantitative method. The object of the research is individual taxpayers at Pamulang University, specifically the Undergraduate Accounting Study Program, semesters 1 to 8. The population of this research was 6,617 students in November 2023 using the Accidental Sampling sampling technique. The data collection methods used are descriptive analysis, validity test, reliability test, classic assumption test (normality test, multicollinearity test, and heteroscedasticity test), multiple linear analysis, hypothesis testing (f test, t test, and coefficient of determination test) with the help of SPSS software version 25. The results of this research show that Perception of Convenience, Perception of Usefulness, and Security and Confidentiality simultaneously influence the Interest of Individual Taxpayers in Using E-Filing. The results of this research show that Perception of Convenience, Perception of Usefulness, and Security and Confidentiality partially influence the Interest of Individual Taxpayers in Using E-Filing.